A metric to measure dynamic competitive balance with respect to prize concentration - D`Ottaviano, F. (Journal of Sports Analytics, 2019)
This study establishes the k index to measure the level of dynamic competitive balance (CB) in a sports league. It also introduces the concept of memory span in measuring dynamic CB. The k index reflects the contemporaneous level of dynamic CB at each season in the history of a league as equivalent to that of a league where k teams have equal chances of winning the title. All seasons of selected European and South American domestic soccer leagues, continental soccer cups, and those of the NBA were analyzed with respect to their k index.